2012
DOI: 10.1007/s12098-012-0795-8
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Non Enzymatic Antioxidants in Down Syndrome

Abstract: Children with Down syndrome have elevated levels of oxidative stress . Hence antioxidant therapy can be beneficial among them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…, who used the same methodology as ours. On the other hand, conflicting results have demonstrated decreased values of TAOC in saliva and blood plasma of children with DS.…”
Section: Discussionmentioning
confidence: 98%
“…, who used the same methodology as ours. On the other hand, conflicting results have demonstrated decreased values of TAOC in saliva and blood plasma of children with DS.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are not consistent with others studies that found a significantly lower total antioxidant capacity in children with DS when compared to control. [45][46][47] In conclusion, saliva is an important tool for primary diagnosis of a possible systemic oxidative stress in patients with Down's syndrome. The present results showed a significant increase in salivary SOD concentration, MDA levels and total protein content in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…SOD1 protects against the free radical superoxide anion O 2 − by reducing it to hydrogen peroxide (H 2 O 2 ) and O 2 in non-diseased individuals. The over-expression of SOD1 in DS is thought to create an imbalance in the free radical detoxication system leading to oxidative stress (OS) [115-117], which in turn promotes DNA damage and chromosomal nondisjunction that may lead to aneuploidy, and increased cell death contributing to abnormal brain development and mental retardation [114, 118, 119]. …”
Section: Linking Genomic Mosaicism and Brain Diseasesmentioning
confidence: 99%